2020
DOI: 10.2478/aoas-2019-0068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Black Mulberry (Morus nigra) Powder on Growth Performance, Biochemical Parameters, Blood Carotenoid Concentration, and Fillet Color of Rainbow Trout

Abstract: The degree of flesh pigmentation is one of the most important quality criteria dictating the fish market value. It is well known that fish, like other animals, cannot synthesize their own coloring pigments de novo, and must obtain these pigments from their diet. In this study, four levels of black mulberry (Morus nigra) juice powder (BMP) as a natural pigment source were incorporated into a basal diet at concentrations of 0, 0.25, 0.5, and 0.75% and fed to rainbow trout weighing 100±5 g for 8 weeks in triplica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Jiang et al absorption efficiently (Cao et al, 2020). Many additives have been recommended by many researchers to be used as supplements in the appropriate amounts (Wang et al, 2018b;Ahmadifar et al, 2019;Adel et al, 2020;El Basuini et al, 2020). The most important additives are probiotics, prebiotics, medicinal herbs and immunostimulants, which have displayed many essential effects on aquatic animals (Fig.…”
Section: Feed Additives and Intestinal Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al absorption efficiently (Cao et al, 2020). Many additives have been recommended by many researchers to be used as supplements in the appropriate amounts (Wang et al, 2018b;Ahmadifar et al, 2019;Adel et al, 2020;El Basuini et al, 2020). The most important additives are probiotics, prebiotics, medicinal herbs and immunostimulants, which have displayed many essential effects on aquatic animals (Fig.…”
Section: Feed Additives and Intestinal Healthmentioning
confidence: 99%
“…Feed additives are useful substances that can be added in small amounts in diets to improve the physiological and immunological status of aquatic animals (Dawood et al, 2018; Shekarabi et al, 2020). They increase the activity of microbiota in the intestine to perform digestion and absorption efficiently (Cao et al, 2020).…”
Section: Feed Additives and Intestinal Healthmentioning
confidence: 99%
“…The use of medicinal plants and their derivatives in aquaculture is increasing day by day all over the world because of having biodegradable properties [ 20 , 21 , 22 , 23 , 24 ], availability and ease to cultivate, and do not accumulate in animal tissues as a residue [ 25 , 26 ]. Essential oils (EOs) are the secondary metabolites of medicinal plants and possess bioactive properties to be used as a phytotherapeutic agent for sustainable aquaculture [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Weight gain and growth rate are directly correlated with animal capability for digestion and absorption of nutrients (Magouz et al, 2020). Medicinal plants have been used to improve nutrition in human for a long time, and their use has drawn considerable attention in livestock, poultry, and aquatic animals (El-Deep et al, 2019;Saleh et al, 2019;Shekarabi et al, 2019). The current study revealed improved growth performance in fish fed GSE.…”
Section: Discussionmentioning
confidence: 63%